2021
DOI: 10.3390/ijms22168388
|View full text |Cite
|
Sign up to set email alerts
|

Kurarinone Attenuates BLM-Induced Pulmonary Fibrosis via Inhibiting TGF-β Signaling Pathways

Abstract: Idiopathic pulmonary fibrosis (IPF) is a refractory interstitial lung disease for which there is no effective treatment. Although the pathogenesis of IPF is not fully understood, TGF-β and epithelial–mesenchymal transition (EMT) have been shown to be involved in the fibrotic changes of lung tissues. Kurarinone is a prenylated flavonoid isolated from Sophora Flavescens with antioxidant and anti-inflammatory properties. In this study, we investigated the effect of kurarinone on pulmonary fibrosis. Kurarinone sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Moreover, Kur elevated IGF1 abundance and activated the PI3K/Akt signaling pathway in hemin-treated HMC3 cells. Previous reports suggested Kur could inhibit the TGF-β signaling, 7 and inhibition of the TGF-β signaling could result in an increase of IGF-1 in activated microglia. 35 Hence, we hypothesized that the regulation of Kur on IGF1 expression in hemin-treated HMC3 cells was mediated by the TGF-β signaling.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, Kur elevated IGF1 abundance and activated the PI3K/Akt signaling pathway in hemin-treated HMC3 cells. Previous reports suggested Kur could inhibit the TGF-β signaling, 7 and inhibition of the TGF-β signaling could result in an increase of IGF-1 in activated microglia. 35 Hence, we hypothesized that the regulation of Kur on IGF1 expression in hemin-treated HMC3 cells was mediated by the TGF-β signaling.…”
Section: Discussionmentioning
confidence: 95%
“…It can inhibit cell immune response and resist oxidative stress 5,6 . In addition, Kur could diminish bleomycin‐tempted pulmonary fibrosis through constraining transforming growth factor beta (TGF‐β) signaling pathways 7 . Moreover, Sun et al confirmed that Kur might be a prospective medicine for the treatment of Parkinson's disease by modulating soluble epoxide hydrolase 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, TGF-β-induced EMT contributes to the development of IPF as the central activator. We previously showed that kurarinone has an anti-fibrotic effect using our experimental system based on the relationship between TGF-β and epithelial cells [ 62 ]. Using our experimental condition, theophylline decreased TGF-β-induced pro-fibrotic phenotypes in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of IL-8, IL-6, TNF-α, PDGF-AB and TGF-β1 (R&D Systems, Minneapolis, MN, USA) in bronchoalveolar lavage fluid, the content of HYP (MyBiosource, San Diego, CA, USA) per 500 mg of the lung tissue (to assess the collagen content), and the expression levels of total p38 MAPKα and p38 MAPKα (pT180/Y182) (ab221013, Abcam) were determined using an ELISA kit (Thermo Fisher Scientific, Waltham, MA, USA) at an absorbance of 450 nm, according to the manufacturer's instructions. 28 Two replicate wells were considered for each specimen. The expression level of each factor in each sample was determined using the calibration curve of absorbance versus concentration.…”
Section: Classification and Counting Of Cells In Bronchoalveolar Lava...mentioning
confidence: 99%